Development of a rapid visual assessment tool for 1-storey school buildings exposed to severe wind loadings in the Philippines - Acosta, Timothy John S.
The Philippines is susceptible to typhoons with extreme wind speeds. In the recent three years, three super typhoons have already struck the Philippines and have caused catastrophic damages. In the occurrence of super typhoons with wind speeds greater than 250 KPH, evacuation shelters are one of the important factors in post-disaster recovery . Most especially in the provincial areas, school buildings are important facilities due to their capacity to shelter a large population and capacity to serve as a base for relief operations. Thus, pre-disaster assessment of the resilience of school buildings is important for them to withstand extreme wind hazards and for authorities to provide efficient and faster disaster recovery. This study aims to develop a tool that assesses the resilience of existing standard DepEd school buildings to severe wind loadings. The vulnerability assessment is done by first developing a damage band for 1-storey school buildings to predict wind-induced damage for various configurations. The damage prediction model makes use of a component-based approach, a basic system reliability analysis, a knowledge-based expert system & empirical data to determine the vulnerability of the building. The tool is then developed in the form of a user-friendly android application to provide a preliminary assessment which is time efficient. Resilience of the structure are expressed as grades in the tool and derived from the predicted damage or vulnerability at a certain wind speed. The score is then compared to a minimum score to determine if the school building is in need for a level 2 assessment. The score also reflects the urgency for repairs/retrofits to withstand extreme wind speeds, depending on how low the scores are. This would help government authorities in the Philippines in the prioritization of the allocation of financial & human resources in the repair/retrofit of the building envelopes of school buildings. The tool is then validated by local experts and compared with an established rapid visual assessment tool. The primary objective of the developed tool is to recommend a detailed investigation for retrofits while the secondary objective is for the tool to have the ability to serve as a prioritization index for retrofits. The results of the tool were then compared to the assessments of a total of 7 experts to find an average level of agreement of O. 6327 (Good Agreement). For the secondary objective, a Kendall's coefficient of Concordance (W) was computed at 0.6804 (Good Agreement).